Bridging the gaps: Unraveling the impact of snow properties on brine wicking and runoff - Anton Komarov; Clement Soriot; Robbie Mallett; Rosemary Willatt; John Yackel; Matthew Sturm; Julienne Stroeve (Journal of Glaciology)
Brine migration from sea ice into the overlying snowpack is relatively understudied yet can significantly modify thermodynamic and electromagnetic properties of the snow. In this study, we investigate the impact of snow properties on brine wicking and runoff by producing samples of four distinctly different snow types (soft wind slab, hard wind slab, faceted grains and melt-freeze clusters) and monitor changes in snow properties after adding brine. The results illustrate that snow grain type and density have a pronounced effect on the height of brine wicking and runoff, snow compaction rates and salt concentrations. In all samples, we observed separation of the initial brine-saturated slush layer into two sublayers with distinctly different properties: solid saline snow-ice at the bottom and less saline brine-wetted snow above it. The maximum height of brine wicking ranged from 6.5 cm in faceted snow to 8.9 cm in hard wind slab samples, which was equivalent of 40 to 50% of total samples’ height. The volume and timing of brine runoff varied between samples, occurring later and in smaller volumes in hard wind slab compared to soft wind slab and coarse-grained samples.